A distinct magnetic anisotropy enhancement in mononuclear dysprosium–sulfur complexes by controlling the Dy-ligand bond length. Issue 19 (19th April 2016) - Liu, Shan-Shan; Lang, Ke; Zhang, Yi-Quan; Yang, Qian; Wang, Bing-Wu; Gao, Song
Abstract : A significant enhancement of magnetic anisotropy is achieved by replacing two of the S-based ligands of a field-induced SIM [(dtc)3 Dy(phen)] with O-based ligands, dbm − ligands, yielding a rarely reported sulfur-ligated Ln–SIM [(dbm)2 Dy(dtc)(phen)]. Abstract : In a field-induced single-ion magnet [(dtc)3 Dy(phen)] (dtc − = diethyldithiocarbamate anion), replacing two of the S-based dtc − ligands with O-based dbm − ligands (dbm − = dibenzoylmethanoate anion) leads to a significant enhancement of magnetic anisotropy, yielding a rarely reported sulfur-ligated lanthanide-based single-ion magnet [(dbm)2 Dy(dtc)(phen)]. Ab initio calculations reveal that the g z value of [(dbm)2 Dy(dtc)(phen)] is much larger than that of [(dtc)3 Dy(phen)], consistent with the experimental results.